Isolation and characterization of chitosans from different fungi with special emphasis on zygomycetous dimorphic fungus benjaminiella poitrasii: evaluation of its chitosan nanoparticles for the inhibition of human pathogenic fungi - Mane, Shamala; Pathan, Ejaj; Tupe, Santosh; Deshmukh, Sneha; Kale, Deepika; Ghormade, Vandana; Chaudhari, Bhushan; Deshpande, Mukund (Biomacromolecules, 2022)
The cell wall chitosan was extracted from fungi belonging to different taxonomic classes, namely, Benjaminiella poitrasii (Zygomycetes, dimorphic), Hanseniaspora guilliermondii, Issatchenkia orientalis, Pichia membranifaciens, and Saccharomyces cerevisiae (Ascomycetes, yeasts), and Agaricus bisporus and Pleurotus sajor-caju (Basidiomycetes). The maximum yield of chitosan was 60.89 ± 2.30 mg/g of dry mycelial biomass of B. poitrasii. The degree of deacetylation (DDA) of chitosan extracted from different fungi, as observed with 1H NMR, was in the range of 70–93%. B. poitrasii chitosan exhibited the highest DDA (92.78%). The characteristic absorption bands were observed at 3450, 1650, 1420, 1320, and 1035 cm–1 by FTIR. Compared to chitosan from marine sources (molecular weight, MW, 585 kDa), fungal chitosans showed lower MW (6.21–46.33 kDa). Further, to improve the efficacy of B. poitrasii chitosan (Bp), nanoparticles (Np) were synthesized using the ionic gelation method and characterized by dynamic light scattering (DLS). For yeast and hyphal chitosan nanoparticles (BpYCNp and BpHCNp), the average particle size was <200 nm with polydispersity index of 0.341 ± 0.03 and 0.388 ± 0.002, respectively, and the zeta potential values were 21.64 ± 0.34 and 24.48 ± 1.58 mV, respectively. The B. poitrasii chitosans and their nanoparticles were further evaluated for antifungal activity against human pathogenic Candida albicans ATCC 10231, Candida glabrata NCYC 388, Candida tropicalis ATCC 750, Cryptococcus neoformans ATCC 34664, and Aspergillus niger ATCC 10578. BpHCNps showed lower MIC90 values (0.025–0.4 mg/mL) than the chitosan polymer against the tested human pathogens. The study suggested that nanoformulation of fungal chitosan, which has low molecular weight and high % DDA, is desirable for antifungal applications against human pathogens. Moreover, chitosans as well as their nanoparticles were found to be hemocompatible and are therefore safe for healthcare applications.